VARIABILITY IN LEVELS OF LOW-DENSITY LIPOPROTEINS CHOLESTEROL IN PATIENTS WITH FAMILIAL HYPERCHOLESTEROLEMIA DEPENDING ON AGE AND SEX AND ITS IMPORTANCE IN THE DIAGNOSIS OF THIS DISEASE - V. А. Korneva; T. Yu. Kuznetsova; G. P. Tihova (Рациональная фармакотерапия в кардиологии, 2017)
Aim. To study the ranges of low density lipoprotein (LDL) cholesterol depending on the age and gender of patients with familial hypercholesterolemia (FHC) by an example of a sample of patients living in the Republic of Karelia.Material and methods. Parameters of lipid spectrum of 219 patients (aged 52.5±1.7 years; males 38.3%) with heterozygous FHC were studied before the start of statin therapy. Definite FHC was diagnosed in 102 patients. Lipid profile was estimated by enzymatic calorimetric method. The diagnosis of FHC was established according to the criteria of The Dutch Lipid Clinic Network.  Genetic analysis was performed in 102 patients (46.6%); pathogenic mutation in the LDL receptor was identified in 21 patients. The control group consisted of 539 people with the excluded diagnosis of FHC (aged 46.8±0.8 years; males 53.8%).Results. We determined the level of LDL cholesterol (LDLC) associated with increased frequency of mutations of the LDL receptor in patients with definite FHC; mutation frequency was 3 times higher when LDLC level was more than 6.5 mmol/L. We revealed the following characteristic intervals of the LDLC levels in patients with a definite FHC: up to 20 years old – 4.8-6.2 mmol/l; in patients of 20-29 years old – 5.9-8.2 mmol/l; in the age range of 30-39 years the upper value of the LDLC levels reached 9.6 mmol/l; in individuals of 40-49 years old a stabilization, "plateau", was observed – LDLC level did not differ significantly compared to the previous decade, and was 5.4-9.0 mmol/l. In the age range  of 50-59 years the upper LDLC level was up to 11.4 mmol/l. Similar indicators were identified in patients aged 60-69 years. Patients older than 70 years with a definite FHC an upper level of LDLC was higher and reached 12.5 mmol/l. Tendency to increase in the characteristic values of LDLC with age was observed both in men and in women. Specific age-related trends  for men (an increase from a plateau by the age of 50 years, with some decrease after 60 years) and women (smooth increase of LDLC levels with age) were demonstrated.Conclusion. Characteristic values of LDLC levels for the Russian population of patients with FHС were shown; relationship between LDLC levels and detection of mutations of the LDL receptor was analyzed.